2003
DOI: 10.4161/cc.2.5.482
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human Cdc25A Stability by Serine 75 Phosphorylation Is Not Sufficient to Activate a S-phase Checkpoint

Abstract: Degradation of Cdc25A phosphatase is an ubiquitous feature of stress. There are some discrepancies in the reported roles for different phosphorylation sites in the regulation of Cdc25A stability. Using a panel of doxycycline-inducible phosphorylation mutants we show that the stability of human Cdc25A protein is dependent upon phosphorylation at S75. In non-stressed conditions and in non-mitotic cells, Cdc25A is unstable and its stability is regulated in a Chk1-dependent manner. During mitosis, Cdc25A becomes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 20 publications
8
88
2
2
Order By: Relevance
“…Two types of kinases are currently known to perform this task in somatic cells: p38 MAP kinase [15] and the checkpoint kinases Chk1 and Chk2 [5]. We found that all three Cdc25A-phosphorylating kinases are activated by phosphorylation in hESCs, and at least in the case of p38, this is detectable by an anti-phosphoresidue antibody.…”
Section: Cdc25a Not P21 Is Involved In Cdk2 Inactivation Upon Dna Dmentioning
confidence: 67%
See 1 more Smart Citation
“…Two types of kinases are currently known to perform this task in somatic cells: p38 MAP kinase [15] and the checkpoint kinases Chk1 and Chk2 [5]. We found that all three Cdc25A-phosphorylating kinases are activated by phosphorylation in hESCs, and at least in the case of p38, this is detectable by an anti-phosphoresidue antibody.…”
Section: Cdc25a Not P21 Is Involved In Cdk2 Inactivation Upon Dna Dmentioning
confidence: 67%
“…Abbreviation: hESC, human embryonic stem cell; UVC, ultraviolet radiation-C range. Although Chk1 and Chk2 can functionally substitute for one another, since the degradation of Cdc25A is prevented and UVC-induced cell cycle block is abrogated only when the activity of both is eliminated, two other kinases that are capable of phosphorylating Cdc25A, p38 and GSK-3b [15,34], do not phosphorylate Cdc25A in UVC-treated hESCs (inhibition of GSK-3b by lithium chloride, data not shown). In this context, the recent finding that GSK-3b is responsible for Cdc25A phosphorylation in c-irradiated mouse ESCs is of note [17].…”
Section: For the Experimental Design) (D-f)mentioning
confidence: 98%
“…This result indicates that even after elimination of p16 expression as the primary block to tumor development, secondary mechanisms that contribute to tumor resistance in Ppm1d -/-mice still operated. Thus, Ppm1d deficiency through activation of p38 MAPK could target other molecules that may negatively contribute to proliferation, such as inhibition of Cdc25 phosphatases 9,10,28 or induction of p19. Thus, we propose that p38 MAPK-dependent modulation of cell cycle regulators including expression of the Cdkn2a locus, through inactivation or depletion of Wip1, will be a powerful approach to treating human primary breast cancers as well as other human malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the p38 MAPK pathway has been implicated as a negative regulator of cell cycle progression by several mechanisms, which implies that Wip1 is also an important regulator of cell cycle progression. p38 MAP kinase inhibits expression of D-type cyclins at transcriptional and post-translational levels 7,8 , phosphorylates and induces degradation of the Cdc25A phosphatase 9 , inhibits the Cdc25B phosphatase through phosphorylation of 14-3-3 sites 10 and phosphorylates the p53 tumor suppressor on two activating sites (Ser33 and Ser46) in the N-terminal region, which contribute to p53-mediated apoptosis 2,11 . Together, these p38 MAPK targets cooperate to activate cell cycle checkpoints, which implies that defects in p38 MAPK regulation or function may perturb cell cycle progression leading to increased tumorigenesis.…”
mentioning
confidence: 99%
“…The same group demonstrated that Ser 76 mediates Cdc25A stabilization in response to UV-induced DNA damage. Moreover, Goloudina et al (2003), using phosphositespecific antibodies, showed that Chk1 and p38 kinase can phosphorylate both Ser 76 and 124, upon UVmediated DNA damage and osmotic stress, respectively ( Figure 1 and Table 1). However, mutations at these sites did not result in an RDS phenotype, raising the question as to whether other mechanisms acting on Cdc25A or related pathways contribute to the S-phase checkpoint.…”
Section: Cdc25a and Checkpointsmentioning
confidence: 99%